Les semences - Turner, Michael (éditions Quae, 2013)
A complete guide on seed production and distribution in tropical regions: technical aspects and organisation of seed production, basic principles for plant improvement and seed biology, management of operations relating to seed production, harvesting and post-harvest conditioning. It also deals with rules for placing on the market of seed and the management of seed breeding companies.